Photolithography based achromatic metasurface/metalens - Gan, Shiyu (Nanyang Technological University, 2023)
A metalens is a type of flat lens that is made using nanostructures to control the phase of light passing through it. These nanostructures are typically made using materials such as silicon or titanium dioxide, and are patterned using methods such as photolithography or electron beam lithography. One of the key advantages of metalenses is that they can be made much thinner and more compact than traditional lenses, which can be useful for applications such as smartphones and other portable devices. Additionally, metalenses can also be made to have a much wider field of view than traditional lenses, which can be useful for cameras and other imaging systems. However, there are also some limitations to metalenses. For example, they currently have a lower transmission efficiency than traditional lenses, which can limit their use in certain applications. Additionally, they also currently have a limited ability to focus light at different wavelengths, which can also limit their use in certain applications. Overall, metalenses are a promising technology that has the potential to revolutionize the field of optics and imaging, but further research and development is needed to overcome some of the current limitations.